Vitamin D Deficiency Is Not Associated with Diabetic Retinopathy or Maculopathy. (14th January 2016) - Alam, Uazman; Amjad, Yasar; Chan, Anges Wan Shan; Asghar, Omar; Petropoulos, Ioannis N.; Malik, Rayaz A.
Abstract : Background . Experimental and clinical studies suggest a possible association between vitamin D deficiency and both diabetic retinopathy and maculopathy. Methods . We have performed a cross-sectional study in adults with types 1 and 2 diabetes mellitus. The relationship between the presence and severity of diabetic retinopathy and maculopathy with serum 25-hydroxyvitamin D concentration was evaluated using logistic regression analyses in the presence of demographic and clinical covariates. Results . 657 adults with diabetes were stratified based on retinopathy grading: No Diabetic Retinopathy (39%), Background Diabetic Retinopathy (37%), Preproliferative Diabetic Retinopathy (21%), and Proliferative Diabetic Retinopathy (3%), respectively. There were no differences in serum 25-hydroxyvitamin D concentrations (25(OH)D) between the groups (15.3 ± 9.0 versus16.4 ± 10.5 versus15.9 ± 10.4 versus15.7 ± 8.5 ng/mL, P = N S ). Logistic regression analysis demonstrated no statistically significant relationship between the severity of retinopathy and serum 25(OH)D. Furthermore, there was no difference in serum 25(OH)D between those with (n = 94, 14%) and those without (n = 563, 86%) Diabetic Maculopathy (16.2 ± 10.0 versus15.8 ± 9.8, P = N S ) and no relationship was demonstrated by logistic regression analyses between the two variables. Conclusions . This study has found no association between serum 25(OH)D and the presence and severity of diabetic retinopathy or maculopathy.